Geochemical characterization of different phases of phosphate sludge waste according to their density in seawater - Daouda Sama; Pamane Kpiagou; M’bènibé Gmakouba; Laounwi Lakmon; Agbessi Gerard Gnagamago; Kissao Gnandi (Discover Water)
Abstract Phosphate treatment at the Kpémé plant uses hydrocycloning with seawater, which produces phosphate sludge wastes discharged into the sea without any prior treatment. This waste is highly enriched in trace elements and is the source of water and coastal sediment pollution. The objective of this study is to highlight the pollutant load of the different phases of phosphate mud mining waste and their possible impact on the marine environment of the Togolese coast and certain neighboring countries, depending on their density. The methodology consists of a classification using a mini hydrocyclone Galaxi–Tower and a geochemical characterization of the phases of these sludgy mining wastes. A study of the bulk density of the phases obtained shows that the apatite-rich phase is denser than the clay-rich phase. Clay-rich phases will be transported over longer distances than apatite-rich phases, in accordance with the sea environment conditions prevailing on the coast. The clay-rich phase has a higher degree of acidity and redox potential than the apatite-rich phase. These phosphate sludgy wastes and the various phases are enriched in Cr, Cd, Cu, Co, Zn, Ni and Hg compared with the earth’s crust. On the other hand, the light phase is more enriched in trace elements than the apatite-rich phase. The light phase has a higher apparent partition coefficient for all elements than the apatite-rich phase, except for Cd and Zn. In the dissolved solutions of clay-rich phases, Fe, Zn and Hg contents are higher than in apatite-rich phases. In contrast, Al, Cr, Cd, Cu and Ni contents are higher in apatite-rich phases than in clay-rich phases.